O impacto de fatores étnico-raciais na resposta clínica a medicamentos antineoplásicos para registro pela ANVISA - Sousa, Claudiosvam Martins Alves de (2019)
Many brazilian patients may not benefit from new drugs as they might, or may even be at risk of being affected by serious adverse events because of genetic variation. This is particularly relevant for cancer chemotherapy, because it is a therapeutic modality in which one coexists with a high incidence of toxicity, sometimes due to lack of response, which with undesirable frequency leads to severe morbidity or even death. Racial and ethnic differences explain at least part of the interindividual variability in clinical response and susceptibility to drug toxicity. Therefore, between 1980s and 1990s, important Asian regulatory authorities, required that clinical trials were conducted in the local population, as a condition for a drug registration in asian countries. Currently, these countries adopt alternative strategies to complete clinical development in the local population. The Brazilian population, because it is considered one of the most miscegenated in the world, becomes a relevant source of genetic variation and variability in clinical response and susceptibility to drug toxicity, however, it is still considered under-represented in pharmacogenomic studies. Thus, the purpose of this research, is to demonstrate the relevance of the elaboration of a regulatory instrument that establishes criteria for the acceptability of foreign clinical data, for drugs registration by Anvisa. According to the Health Surveillance Data System (Datavisa), 184 drugs were registered between 2014 and 2018, of which 48 (25%) were antineoplastic drugs, where 21 (43.8%) of them were registered based on foreign clinical data. In the package inserts of these 21 antineoplastic drugs, FDA alerts on clinical response variability due to ethnic-racial differences are often absent and when present, they specifically refer the pharmacogenomic profile of the local population. Pharmacovigilance systems (Notivisa and Vigilyze®) did not present sufficient numbers of reports to identify the association between variability in the clinical response to antineoplastic drugs and ethnic-racial differences.